Focused Written Feedback on Developing Quality Bachelor’s Thesis Proposal - Supriyadi, Supriyadi; Kholid, Muhammad Ridho (Universitas Islam Negeri Raden Intan Lampung, 2020)
The effectiveness of written feedback in learning is a debatable topic that divides opinion. Many researchers claim that written feedback does not have a significant effect on improving students’ learning achievement. However, many other researchers indicate otherwise. This research aimed to analyze the effect of using focused written feedback (FWF) on students’ writing skills. This research sample consisted of 10 students taught through practice to write a bachelor's thesis proposal. This research employed the equivalent time-series design. Observations were employed in a four-time series. There are four models for the implementation of focused written feedback: task feedback (FT), process feedback (FP), self-regulation feedback (FR), and self-feedback (FS). Then, there are three major questions: what are the goals? (Feed-up), what progress is being made toward the goal? (Feedback), what activities need to be undertaken to make better progress? (Feed-forward). The instruments of this study were written feedback assessment guidelines, and rubrics for assessing writing skills. The researchers had checked both instruments. The result showed that students’ writing skills improved the most in the section where they received the most practice. In conclusion, this study contributed to effective written feedback and provided some implications for lectures.